2015
DOI: 10.1074/jbc.m115.643742
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Growth Regulatory Roles of Protein Kinase D Isoforms in Human Keratinocytes

Abstract: Background:The role of protein kinase D (PKD) signaling in human epidermis is unclear. Results: PKD isoforms have distinct and opposing growth regulatory functions in human keratinocytes. PKD3 is down-regulated upon differentiation and PKD3 silencing results in loss of keratinocyte proliferative potential. Conclusion: PKD signaling is essential for maintaining human epidermal homeostasis. Significance: PKD3 represents a potential drug target in hyperproliferative skin disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In fact, PKD1 was initially described to be expressed throughout the superbasal layers with a predominant expression in the stratum basalis, in accordance with its proproliferative role as previously described in mice (37). However, further results indicated that PKD1 was not detected in human keratinocytes, these cells being more dependent on the two other isoforms of the PKD family, PKD2 (prodifferentiative), and PKD3 (proproliferative), for their proliferation (38). As hypothesized by the authors, such discrepancies could be the consequence of a certain lack of specificity of the antibodies used by Ristich and colleagues (37) because sc-935 antibody has been reported by others to cross-react with PKD2 in Western blot analyses (39).…”
Section: Pkd1 As a Proproliferative And Prosurvival Factor In Skin Casupporting
confidence: 75%
“…In fact, PKD1 was initially described to be expressed throughout the superbasal layers with a predominant expression in the stratum basalis, in accordance with its proproliferative role as previously described in mice (37). However, further results indicated that PKD1 was not detected in human keratinocytes, these cells being more dependent on the two other isoforms of the PKD family, PKD2 (prodifferentiative), and PKD3 (proproliferative), for their proliferation (38). As hypothesized by the authors, such discrepancies could be the consequence of a certain lack of specificity of the antibodies used by Ristich and colleagues (37) because sc-935 antibody has been reported by others to cross-react with PKD2 in Western blot analyses (39).…”
Section: Pkd1 As a Proproliferative And Prosurvival Factor In Skin Casupporting
confidence: 75%
“…An antibody against PKD2 did not produce any immunoblotting reaction, indicating that GT1-7 cells did not express PKD2. An antibody against PKD3 reacted with one protein of the expected molecular weight (31). Of note, the apparent molecular weight of this protein increased slightly after GnRH treatment.…”
Section: Involvement Of Pkc In Gnrh-induced Erk Activation and Erbb4mentioning
confidence: 99%
“…see Ref. 31), and no protein levels were reduced after GnRH or siRNA treatment. From these results, we concluded that this antibody could not detect PKD1 in our experimental conditions.…”
Section: Involvement Of Pkc In Gnrh-induced Erk Activation and Erbb4mentioning
confidence: 99%
“…Using PKD1- conditional knockout (cKO) mouse model, the authors have presented evidence that: 1) keratinocyte cells in PKD1-cKO mice showed delayed wound healing and reduced proliferative response, 2) PKD1 is a positive regulator of epidermal hyperplasia and inflammation in response to phorbol esters and 3) PKD1-cKO mice are resistant to tumor formation when subjected to two-stage chemically-induced skin carcinogenesis [168]. In a recent study, Ryvkin et al have demonstrated an opposing role of PKD2 and PKD3 isoforms in human keratinocyte proliferation and differentiation [169]. The authors have shown that loss of PKD2 resulted in enhanced keratinocyte proliferation suggesting an anti-tumorigenic role of PKD2.…”
Section: Pkd: a Friend Or Foe In Cancer Development And Progression?mentioning
confidence: 99%